IBM Cognos TM1 cookbook : build real world planning, budgeting, and forecasting solutions with a collection of 60 simple but incredibly effective recipes /: build real world planning, budgeting, and forecasting solutions with a collection of 60 simple but incredibly effective recipes. (2011) - Unknown
No abstract available